The role of innovation and development in improving product quality and increasing customer satisfaction in insurance companies in the Kingdom of Saudi Arabia (International Journal of Financial, Administrative and Economic Sciences, 2024)
The goal of this research is to evaluate the influence of innovation and development in boosting product quality and increasing customer satisfaction in insurance firms in the Kingdom of Saudi Arabia. A quantitative technique was adopted, with a sample size of 120 persons. Data were obtained by surveys, and the replies were examined using statistical analytic methods. The findings reveal a considerable influence of product development on enhancing customer experience and boosting customer satisfaction in insurance firms in Saudi Arabia. Additionally, the results show the significance of product development in boosting internal procedures, which also leads to higher customer satisfaction inside these firms. Furthermore, the research reveals that the function of product development in boosting the efficacy of marketing activities is vital in encouraging consumer happiness in the insurance industry. Entirely, the study highlights the vital need of providing insurance solutions that not only suit the requirements of clients but also improve their entire experience. The consequences of these results are deep, as they show that a focus on product innovation may lead to increased operational efficiency and more efficient marketing techniques, which eventually lead to higher customer satisfaction levels. This research adds to the current literature by giving insights into how insurance firms might employ product development to strengthen their competitive edge in the marketplace. By understanding the link between product innovation, internal procedures, marketing effectiveness, and customer happiness, insurance businesses may develop tactics that correspond with consumer expectations and enhance overall service quality. In conclusion, this research stresses the essential importance of product development in the insurance business and its direct association with customer satisfaction in Saudi Arabia. The findings serve as a significant reference for insurance businesses trying to strengthen their product offerings and improve client interactions in an increasingly competitive climate.
Keywords: Innovation; Product Quality; Customer Satisfaction; Insurance Companies